Impact of Online Advertisement on Customer Satisfaction With the Mediating Effect of Brand Knowledge - Salameh, Anas A.; Ijaz, Mahrukh; Omar, Abdullah Bin; Zia ul Haq, Hafiz Muhammad (Frontiers in Psychology, 2022)
This paper aims to describe how online advertisement impacts on customer satisfaction with the mediating effect of brand knowledge. The sample size of this study is based on 100 participants that are in the Multan region. In this research, a data is gathered by conducting different formal & informal interviews. Cross-sectional data gathering techniques are used in this study. Results show that online advertisement having no significant impact on customer satisfaction. But, when the brand knowledge factor is involved as a mediating variable, then the relationship between online advertisement and customer satisfaction will become increases. Online advertisement is a new advertisement tool that is used by the majority of organizations. This paper helps the practitioners to choose the better tools for an online advertisement and also increase the brand knowledge by using different awareness techniques. Through this research, it will be quite an effective approach in front of the company's management to develop the trust level among the customers about their product quality, because such a positive brand reputation will enhance the satisfaction level of the customers. This study is unique in its own way that in previous researches, none of the researchers majorly worked to find out the direct relationship between the online advertisement and customer satisfaction, by considering a brand knowledge factor as a mediating variable. This research highlights important points that will help the upcoming researchers to critically analyze such aspects in their future researches.